Where is it logical to break-up a ureter stone with endoscopic surgery? - Caniklioğlu, Mehmet; Selmi, Volkan; Sarı, Sercan; Öztekin, Ünal; Gürtan, Emin; Işıkay, Levent (Journal of Surgery and Medicine, 2021)
Background/Aim: Today, we have the technology to break up a ureter stone in the ureter, as well as in the renal pelvis, with ureterorenoscopic procedures. In the past, when this option was not available, the surgeons improved several techniques and antiretropulsion devices to let the stone migrate through the renal pelvis. This study was conducted to clarify whether it is more advantageous to dust a stone in the ureter where it is impacted or in a wider area such as the renal pelvis. Methods: The data of 134 patients who underwent semirigid ureterorenoscopy (srURS) due to single and primary upper ureteral stones were included and analyzed in this retrospective cohort study. The patients were divided into two groups according to the development of spontaneous push-up during surgery (Group 1: The non-push-up group, Group 2: The push-up group). Results: While hemoglobin levels lowered significantly in both groups after the surgery, creatinine levels increased (P<0.05). However, there was no significant difference between the groups regarding preoperative or postoperative laboratory findings (P>0.05). Operation times were similar in both groups, in contrast with the literature. Stone-free rates were significantly higher in srURS than in intrarenal surgery (RIRS) (P=0.03). Complication rates were also similar in this study. Conclusion: The application of srURS after fixing an upper ureter stone at its location using a Stone Cone® results in higher stone-free rates than pushing it back to dust it in renal pelvis. We recommend srURS supported by an antiretropulsion method as a treatment for upper ureteral stones.